2010
DOI: 10.1371/journal.pone.0014330
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of ELISpot Assays Demonstrated between Major HIV Network Laboratories

Abstract: BackgroundThe Comprehensive T Cell Vaccine Immune Monitoring Consortium (CTC-VIMC) was created to provide standardized immunogenicity monitoring services for HIV vaccine trials. The ex vivo interferon-gamma (IFN-γ) ELISpot is used extensively as a primary immunogenicity assay to assess T cell-based vaccine candidates in trials for infectious diseases and cancer. Two independent, GCLP-accredited central laboratories of CTC-VIMC routinely use their own standard operating procedures (SOPs) for ELISpot within two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 22 publications
2
48
0
Order By: Relevance
“…In other populations, B*44:02 is a major allele that is often found on the B*44-C*05 haplotype (53). Understanding the early immune responses facilitated by various B*44 alleles should help with the dissection of protective immunity to HIV-1 infection, especially in the context of subtypes A1 and C in sub-Saharan Africa (22). Viral subtypes are highly relevant to the design of vaccines (42,57), and multiple reports have indicated that disease progression may differ somewhat by viral subtype (32,33,40,62,90).…”
Section: Discussionmentioning
confidence: 99%
“…In other populations, B*44:02 is a major allele that is often found on the B*44-C*05 haplotype (53). Understanding the early immune responses facilitated by various B*44 alleles should help with the dissection of protective immunity to HIV-1 infection, especially in the context of subtypes A1 and C in sub-Saharan Africa (22). Viral subtypes are highly relevant to the design of vaccines (42,57), and multiple reports have indicated that disease progression may differ somewhat by viral subtype (32,33,40,62,90).…”
Section: Discussionmentioning
confidence: 99%
“…For all other assays, PBMC were frozen in 90% fetal bovine serum (FBS) and 10% dimethyl sulfoxide (DMSO) using a Kryo 560-16 rate controlled freezer (Planer, Sunbury-On-Thames, United Kingdom) and stored in vapor phase liquid nitrogen. The PBMC for the IFN-␥ ELISPOT assay were plated at 2 ϫ 10 5 viable cells per well in quadruplicate with peptides at 1.5 g/ml, representing the vaccine inserts, as described previously (39)(40)(41). Peptides were synthesized as 15-mers overlapping by 11 amino acids with ϳ90% purity by high-pressure liquid chromatography (HPLC) (AnaSpec Inc., Fremont, CA).…”
Section: Methodsmentioning
confidence: 99%
“…There have been earlier attempts at evaluating ELISpot proficiency panels and assay equivalence (Cox et al, 2005; Boaz et al, 2009; Gill et al, 2010), which focused primarily on positive or negative responses and concordance among labs. The EQAPOL ELISpot program does not have criteria for defining positive or negative responses, rather the goal is to assess how accurate to the consensus average and precise laboratories are using their own in-house assay given standard peptides and samples.…”
Section: Elispot Programmentioning
confidence: 99%